2010
DOI: 10.1073/pnas.1007277107
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal cortex and basal ganglia contributions to visual working memory

Abstract: Visual working memory (VWM) is a remarkable skill dependent on the brain's ability to construct and hold an internal representation of the world for later comparison with an external stimulus. The prefrontal cortex (PFC) and basal ganglia (BG) interact within a cortical and subcortical network supporting VWM. We used scalp electroencephalography in groups of patients with unilateral PFC or BG lesions to provide evidence that these regions play complementary but dissociable roles in VWM. PFC patients show behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
121
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(132 citation statements)
references
References 55 publications
8
121
1
2
Order By: Relevance
“…The bottleneck begins in posterior cortex where neural receptive fields are more restricted to one hemifield than in prefrontal cortex. Human studies report varying degrees of hemifield independence (24)(25)(26)(27). In our task, the need to localize the changed object may emphasize this independence.…”
Section: Discussionmentioning
confidence: 99%
“…The bottleneck begins in posterior cortex where neural receptive fields are more restricted to one hemifield than in prefrontal cortex. Human studies report varying degrees of hemifield independence (24)(25)(26)(27). In our task, the need to localize the changed object may emphasize this independence.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that this "filter activity" was associated with interindividual differences in WM capacity suggests that frontal areas and basal ganglia exert top-down control over WM representations. Evidence from recent clinical studies further underlines the relevance of an intact PFC and basal ganglia for WM performance (Baier et al, 2010;Voytek and Knight, 2010). Thus, top-down control over information selectively encoded and maintained seems to be closely related to a fronto-parietal and fronto-striatal network.…”
Section: Functional Neuroanatomy Of the Working Memory Networkmentioning
confidence: 99%
“…In a recent study investigating patients with unilateral PFC lesions, load modulations of the CDA were only observed ipsilesional, but not contralesional (Voytek and Knight, 2010). The authors suggested that PFC lesions lead to a loss in top-down facilitation contributing to WM performance.…”
Section: The Interplay Of the Two Components Across The Lifespan Reflmentioning
confidence: 99%
“…It, in turn, gets input from the cerebral cortex (42). Striatum is best known for its role in the planning and modulation of movement pathways but is also potentially involved in a wide variety of cognitive processes including executive function, such as working memory, cognitive flexibility, and habit formation (43).…”
Section: Striatummentioning
confidence: 99%